Obesity attenuates inflammation, protein catabolism, dyslipidaemia, and muscle weakness during sepsis, independent of leptin. Issue 1 (7th January 2022) - Vankrunkelsven, Wouter; Derde, Sarah; Gunst, Jan; Vander Perre, Sarah; Declerck, Emiel; Pauwels, Lies; Derese, Inge; Van den Berghe, Greet; Langouche, Lies
Abstract: Background: Muscle weakness is a frequently occurring complication of sepsis, associated with increased morbidity and mortality. Interestingly, obesity attenuates sepsis‐induced muscle wasting and weakness. As the adipokine leptin is strongly elevated in obesity and has been shown to affect muscle homeostasis in non‐septic conditions, we aimed to investigate whether leptin mediates the protective effect of obesity on sepsis‐induced muscle weakness. Methods: In a mouse model of sepsis, we investigated the effects of genetic leptin inactivation in obese mice (leptin‐deficient obese mice vs. diet‐induced obese mice) and of leptin supplementation in lean mice ( n = 110). We assessed impact on survival, body weight and composition, markers of muscle wasting and weakness, inflammation, and lipid metabolism. In human lean and overweight/obese intensive care unit (ICU) patients, we assessed markers of protein catabolism ( n = 1388) and serum leptin ( n = 150). Results: Sepsis mortality was highest in leptin‐deficient obese mice (53% vs. 23% in diet‐induced obese mice and 37% in lean mice, P = 0.03). Irrespective of leptin, after 5 days of sepsis, lean mice lost double the amount of lean body mass than obese mice ( P < 0.0005). Also, irrespective of leptin, obese mice maintained specific muscle force up to healthy levels ( P = 0.3) whereas lean mice suffered from reduced specific muscle force (72% of healthy controls, P < 0.0002). As compared with lean septic mice, both obese septic groups had less muscle atrophy, liver amino acid catabolism, and inflammation with a 50% lower plasma TNFα increase ( P < 0.005). Conversely, again mainly irrespective of leptin, obese mice lost double amount of fat mass than lean mice after 5 days of sepsis ( P < 0.0001), showed signs of increased lipolysis and ketogenesis, and had higher plasma HDL and LDL lipoprotein concentrations ( P ≤ 0.01 for all). Muscle fibre type composition was not altered during sepsis, but a higher atrophy sensitivity of type IIb fibres compared with IIa and IIx fibres was observed, independent of obesity or leptin. After 5 days of critical illness, serum leptin was higher ( P < 0.0001) and the net waste of nitrogen ( P = 0.006) and plasma urea‐to‐creatinine ratio ( P < 0.0001) was lower in overweight/obese compared with lean ICU human patients. Conclusions: Leptin did not mediate the protective effect of obesity against sepsis‐induced muscle wasting and weakness in mice. Instead, obesity—independent of leptin—attenuated inflammation, protein catabolism, and dyslipidaemia, pathways that may play a role in the observed muscle protection.